The role of the principal in fostering al-akhlaq al-karimah among students at smait darul rasyid east lampung - Chusnul Jauhari; Kharis Syuhud Mujahada; Ahmad Ahadi (At Turots: Jurnal Pendidikan Islam, 2025)
The impact of globalization has led to the free entry of Western cultural influences into Indonesia. This development brings both positive and negative effects, especially for the younger generation in the field of education. Students who fail to respond wisely to globalization may experience moral degradation. As the leader in the school environment, the principal holds a significant responsibility in ensuring the success of educational implementation and plays an essential role in shaping students' character through school-based moral development programs to counter the negative effects of rapid globalization. This study focuses on three research questions: (1) What is the current condition of students' moral character at SMAIT Darul Rasyid Lampung Timur? (2) What is the role of the principal in shaping students’ character at SMAIT Darul Rasyid Lampung Timur? (3) What are the supporting and inhibiting factors in the moral development of students at SMAIT Darul Rasyid Lampung Timur? This research employs a descriptive qualitative approach, with data collected through documentation, observation, and interviews. The data were then analyzed by interpreting the collected information to draw meaningful conclusions. The results of the study indicate that the moral condition of students at SMAIT Darul Rasyid still presents several issues, particularly regarding student discipline in implementing the 5S culture (Smile, Greet, Salute, Politeness, and Courtesy). The principal plays a vital role in shaping students’ morals through school culture, which includes seven leadership roles: as an educator, by providing moral advice during flag ceremonies; as a manager, by implementing management functions (POAC) through programs such as Dhuha prayer, short religious talks (kultum), Qur'an recitation, prayer routines, and ceremonies aligned with the school’s vision and mission; as an administrator, by recording student violations in a disciplinary logbook; as a supervisor, by monitoring teachers’ implementation of daily prayers and student pledges; as a leader, by delegating authority and leading activities such as Dhuha prayer and flag ceremonies; as an innovator, by scheduling regular moral development activities; and as a motivator, by encouraging teachers and staff during ceremonial events. The supporting factors in students’ moral development through school culture include teacher involvement and community support, while the inhibiting factors involve students’ individual personalities and limited knowledge about moral and ethical values (akhlaqul karimah)